Optical coherence tomography using algebraic reconstruction technique with l1-optimization - Seck, Hon Luen (2014)
Optical coherence tomography (OCT) is an imaging modality for obtaining tomography images of subsurface structures. While primarily invented and widely used for the imaging of biological tissues, it can equally be used to perform non-destructive inspection of industrial parts. With rapid advancement of 3D manufacturing technology, non-destructive subsurface inspection has become an important issue and OCT can play important roles in these industrial applications. Hence, the development of new OCT methods for industrial inspection has attracted increasing attention in addition to the traditional applications of OCT in bio-imaging.